The Effect Of Brand Image and Celebrity Endorser on "Wardah" Indonesian Halal Body Cream Cosmetics’ Purchase Decisions - Riri Oktarini (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the effect of Brand Image and Celebrity Endorser on the Purchase Decision. Indonesian Halal Body Cream Cosmetics of Wardah brand chosen as the context for this research. Empirical data were collected through a survey of 96 working mothers in South Tangerang Region. The quantitative method used is explanatory research using statistical analysis techniques through multiple linear regression analysis including correlation, determination, and hypothesis testing. The result of this study shows that “Brand Image” has a significant effect on purchasing decisions by 41.1%, while “Celebrity endorsers” also have a significant effect on purchasing decisions by 36.0%.